Deep genealogical analysis of a large cohort of participants in the CARTaGENE project (Quebec, Canada) - Marc Tremblay; Gabrielle Rouleau (Annals of Human Biology, 2017)
Background: Genealogical analysis helps to better understand the genetic structure of populations. The population of Quebec (Canada) often serves as a model for this type of analysis, having one of the world’s most complete genealogical databases. Aim: The main objective of this study was to reconstruct, analyse and compare the ascending genealogies of participants to CARTaGENE, a project that aims at building a database on various aspects of public health. Subjects and methods: In total, 5110 genealogies from four Quebec regions were reconstructed. Distribution of ancestors, completeness and depth of the genealogies, characteristics of immigrant ancestors and kinship and inbreeding coefficients were analysed. Results: Most genealogies go back to the 17th century, with a mean genealogical depth of 10 generations. Origins of immigrant ancestors are more diverse in the Montreal region, resulting in lower inbreeding and kinship among the participants from this region. Inbreeding and kinship values are mainly explained by remote genealogical links (from 6 to 11 generations). Conclusion: Deep genealogies allowed for a precise measurement of the geographic origins of the participants’ immigrant ancestors, as well as inbreeding and kinship ties in the population, which may be crucial for studies aiming to identify genetic variations associated with Mendelian or complex diseases.